1997
DOI: 10.2337/diab.46.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Reduces Contraction by Inhibition of Vascular Smooth Muscle Cell Ca2+ Currents and Not Endothelial Nitric Oxide Production

Abstract: The insulin-sensitizing compound troglitazone has evolved into a promising therapeutic agent for type II diabetes. It improves insulin sensitivity and lipoprotein metabolic profiles and lowers blood pressure in humans and rodents. Because troglitazone has insulin-like effects on a number of tissues, we hypothesized that it may reduce vascular tone through stimulation of endothelial-derived nitric oxide (NO) production or by diminution of vascular smooth muscle cell (VSMC) intracellular calcium ([Ca2+]i). Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 40 publications
1
46
2
4
Order By: Relevance
“…Thus, the explanation for the observed increase in muscle blood flow among lean Ala12 carriers is unclear. PPARγ activation is known to modify vascular responsiveness in vivo [31][32][33] and in vitro [34][35][36], but the effect of PPARγ2 Pro12Ala polymorphism has never been assessed previously. Thus, Ala12 carriers appear to have a constitutively higher blood flow compared with Pro12 homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the explanation for the observed increase in muscle blood flow among lean Ala12 carriers is unclear. PPARγ activation is known to modify vascular responsiveness in vivo [31][32][33] and in vitro [34][35][36], but the effect of PPARγ2 Pro12Ala polymorphism has never been assessed previously. Thus, Ala12 carriers appear to have a constitutively higher blood flow compared with Pro12 homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Research in animal models has shown that troglitazone and pioglitazone caused peripheral vasodilation, which was mediated by prostaglandin production associated with increased calcium fluxes in smooth muscle (85,86). There also may be differential effects between rosiglitazone and troglitazone on human small arteries (87).…”
Section: Effects Of Reducingmentioning
confidence: 99%
“…Interestingly, Shargorodsky et al (35) did report that rosiglitazone lowers systemic vascular resistance. Apart from a potentiation of insulin effect, rosiglitazone may induce vasodilatation by inhibition of calcium currents (36,37), reduction of endothelin-1 secretion (38), or downregulation of the sympathetic nervous system (39).…”
Section: Characterization Of Subject With Tzd-induced Edemamentioning
confidence: 99%